Strategi Pengembangan Usaha Jamur Tiram dengan Analisis SWOT pada Studi Kasus “Warung Jamur Mang Yayat” - Aini Dewi Maryan; Adenty Oktaviani; D Yadi Heryadi (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
Starting a business is an easy job and can be done by anyone, the most important thing is strong beliefs and values ​​for independent business, a strong will to become an entrepreneur is not enough. Good business development starts from ourselves, even though we face many obstacles in the business world, therefore a strategy is needed in business development so that the business can last a long time. One of the current businesses that is very prospective and has potential is cultivating edible mushrooms, one of which is oyster mushrooms which are well known to the public and are a type that has high efficacy. "Warung Mushroom Mang Yayat" was chosen as the research object for several reasons, that this business has succeeded in surviving and developing amidst intense competition. The aim of this research is to analyze the SWOT strategy and analyze the development strategy of "Warung Mushroom Mang Yayat". SWOT (Strengths, Weakness, Opportunities, and Threats) analysis is a method for developing business strategies. The results of this research indicate that "Warung Mushroom Mang Yayat" can improve service and product quality using SWOT analysis. Despite several existing threats and weaknesses, "Warung Mushroom Mang Yayat" is able to continue to develop to this day.